Ucinnost anti-tNF-alpha léciv v bĕzné klinické praxi a náklady na tato léciva - Prokes, M (Vnitrni lekarstvi, 2009)
A comparison of effectiveness of TNF antagonists adalimumab, infliximab and etanercept in the treatment of rheumatoid arthritis (RA) was made, which was derived from studies provided abroad based on routine clinical practice. The calculation of cost-effectiveness of each TNF antagonist for Czech Republic was made on the basis of Dutch DREAM registry of patients with RA (Kiewit et al, 2008). The prices of therapy of all three TNF antagonists are similar in the first year of treatment of patients with average weight, in the second year the price of infliximab is lower, but only in the case of patients where the doses do not reach 4 amp. of infliximab. Clinical effectiveness was evaluated in DAS28 and HAQ units. Cost-effectiveness of all TNF antagonists was similar, when 2 amp. of infliximab per dose phycician considered sufficient, but when patients were given higher doses of infliximab the trend to lower cost-effectiveness of infliximab compared to adalimumab and etanercept was observed.
Keywords: analýza nákladů a výnosů; imunoglobulin G; Česká republika; Adalimumab; Tumor Necrosis Factor-alpha; monoklonální protilátky; infliximab; Antibodies, Monoclonal; Cost-Benefit Analysis; Czech Republic; Infliximab; adalimumab; TNF-alfa; Immunoglobulin G; Humans; antirevmatika; receptory TNF; Antibodies, Monoclonal, Humanized; humanizované monoklonální protilátky; etanercept; Arthritis, Rheumatoid; revmatoidní artritida; Antirheumatic Agents; Etanercept; Receptors, Tumor Necrosis Factor; lidé